Ocular syndromes secondary to feline herpesvirus-1 infection-Review - Oria, A. P.; Silveira, C. P. B. [UNESP]; Souza, M. R. de; Pinna, M. H.; Costa-Neto, J. M.; Dorea Neto, F. A. (Univ Federal Rural Pernambuco, 2012)
The feline infectious respiratory disease is the most common diagnosed infection in the veterinary clinic routine, being the Feline Herpesvirus1 the most important causal agent. Once infected, the cat will become a lifetime latent carrier, experiencing episodes of viral reactivation and spontaneous spread especially when there is a stress factor involved. This virus acts in the upper respiratory system and is also associated with eye diseases. The diagnosis is made by viral isolation and treatment protocol is based on a topic antiviral therapy, even though many of them are epiteliotoxic and may progress with intense discomfort in felines. The purpose of this paper is to describe the main ocular manifestations and syndromes seen in cats suffering from feline herpesvirus. Conjunctivitis, epithelial and stromal keratitis, corneal ulceration and indolent ulcers are the main ocular manifestations associated with viral infection, whereas symblepharon, keratoconjunctivitis sicca, proliferative keratitis and corneal sequestration are the main eye syndromes that can be observed in infected animals.
Keywords: oftalmology; viral diseases; treatment